The Language Experience Approach Teaching Reading - Illinois State Office of the Superintendent of Public Instruction, Springfield; Illinois State Office of the Superintendent of Public Instruction, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
An overview of the language experience approach and suggestions for implementing it at all levels of instruction are presented in this booklet. Based on the assumption that it is impossible to isolate reading instruction from other language functions, a multimethod approach is described which focuses on the linguistic, conceptual, and perceptual experiences of children. The following topics are discussed: history and rationale of the language experience approach, beginning reading instruction, the classroom as a learning laboratory, organization for learning, the language experience approach in upper elementary, middle, and high schools, adult literacy programs, and bilingual programs. (LL)
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Literacy; Beginning Reading; Bilingual Students; Class Organization; Elementary Secondary Education; Language Experience Approach; Language Usage; Reading Instruction; Teaching Methods; Guides, General